User-generated content and influencer marketing involving e-cigarettes on social media: a scoping review and content analysis of YouTube and Instagram - Marissa J. Smith; Christina Buckton; Chris Patterson; Shona Hilton (BMC, 2023)
Abstract Background Evidence suggests that experimentation with e-cigarettes among young people is increasing. Social media is widely used by young people with user-generated content and influencer marketing particularly influential in promoting products. This paper documents a snapshot of online user-generated content and influencer marketing related to e-cigarettes on YouTube and Instagram. Methods Scoping review of relevant e-cigarette-related content on two social media platforms popular with youths, YouTube and Instagram, between June and August 2021. Content analysis was undertaken to examine text, audio, and video content, recording age restrictions, health warnings, page characteristics, and post characteristics. Narrative post content was coded using a coding frame that was developed inductively in response to emergent categories. Results Vaping was portrayed positively on social media; of the posts analysed, 86.5% (n = 90 of 104) of Instagram posts and 66.0% (n = 64 of 97) of YouTube videos. Warnings about age restrictions and health (e.g., nicotine addiction/toxicity) did not feature in the majority of posts; 43.3% (n = 42) of YouTube videos (n = 42) contained an age warning compared to 20.2% of Instagram posts (n = 21). While 25.8% (n = 25) of YouTube videos and 21.2% of Instagram (n = 22) posts contained a health warning. Conclusion Of concern is the fact that the vast majority of YouTube and Instagram content about e-cigarettes promoted their use, and typically the content does not contain age and/or health warnings. These findings may highlight a priority for governmental policy to restrict the ability of marketers to reach youths with social media content promoting e-cigarettes.